2019
DOI: 10.1096/fj.201901343r
|View full text |Cite
|
Sign up to set email alerts
|

A kinome‐wide screen using a NanoLuc LATS luminescent biosensor identifies ALK as a novel regulator of the Hippo pathway in tumorigenesis and immune evasion

Abstract: The Hippo pathway is an emerging signaling pathway that plays important roles in organ size control, tissue homeostasis, tumorigenesis, metastasis, drug resistance, and immune response. Although many regulators of the Hippo pathway have been reported, the extracellular stimuli and kinase regulators of the Hippo pathway remain largely unknown. To identify novel regulars of the Hippo pathway, in this study we created the first ultra‐bright NanoLuc biosensor (BS) to monitor the activity of large tumor suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…With regard to the mechanisms underlying ALK fusion-induced PD-L1 in NSCLC, several studies demonstrated the involvement of PI3K and MAPK activation [47], as well as the Hippo pathway [52]. Through a kinome-wide screen of modulators of the Hippo pathway, Nouri et al identified ALK as an inducer of the new ALK-LATS-YAP-PD-L1 axis in NSCLC cells expressing EML4-ALK.…”
Section: Alk Aberrations and Immune Evasion Signalingmentioning
confidence: 99%
“…With regard to the mechanisms underlying ALK fusion-induced PD-L1 in NSCLC, several studies demonstrated the involvement of PI3K and MAPK activation [47], as well as the Hippo pathway [52]. Through a kinome-wide screen of modulators of the Hippo pathway, Nouri et al identified ALK as an inducer of the new ALK-LATS-YAP-PD-L1 axis in NSCLC cells expressing EML4-ALK.…”
Section: Alk Aberrations and Immune Evasion Signalingmentioning
confidence: 99%
“…First we co-transfected SmBiT-ACE2 or LgBiT-RBD with LgBiT-YAP15 or SmBiT-14-3-3, respectively. While the YAP15 and 14-3-3 constructs have been previously demonstrated to interact and rescue the NanoBiT structure 11 , these proteins are not known to interact with ACE2 and RBD.…”
Section: Sars-cov-2 Nanobit Biosensor For Detecting Ace2-rbd Interactmentioning
confidence: 98%
“…For the other component we used the soluble ectodomain of ACE2 (residues 1 to 740) as this has been shown to be su cient to interact with RBD 21 . Since RBD is the smaller protein of the two partners of interest 11 , we linked the RBD with the larger fragment of the split luciferase (LgBiT) while ACE2 was fused to the small fragment (SmBiT, Figure 1B). A glycine-serine linker was inserted between ACE2 or RBD and its respective NanoBiT component 11 to enhance folding and exibility of the fusion proteins.…”
Section: Sars-cov-2 Nanobit Biosensor For Detecting Ace2-rbd Interactmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned examples are not the only instances of interconnecting signaling networks between the Hippo pathway and RTKs, as numerous active studies are investigating this relationship. For instance, a recent study uses a novel biosensor [131] to investigate possible regulation of the Hippo by Anaplastic lymphoma kinase (ALK) receptor [132]. ALK is an RTK with notable mRNA expression in the human brain and some other organs [133].…”
Section: Anaplastic Lymphoma Kinase (Alk) a Novel Activatory Relatiomentioning
confidence: 99%